PENGARUH FAKTOR DUKUNGAN KELUARGA DAN FAKTOR BIAYA TERHADAP TERJADINYA PUFA/Pufa PADA ANAK USIA 6-12 TAHUN DI SD NEGERI 023896 BINJAI - Fanny Olivia Pgirsang (Jurnal Mutiara Kesehatan Masyarakat, 2020)
One group at high risk for dental caries is children aged 6-12 years. Dental caries is an i disease that can damage tooth structure, if left untreated, it can involve an open pulp that is the Pulp Involment (P / p), traumatic ulceration around the soft tissue that is Ulcer (U / u), and the pathway for pus caused by pus abscess namely Fistula (F / f), the presence of swelling accompanied by pus namely Abscess (A / a). The purpose of this study is to determine whether or not there is an influence of family support factors and costs on the occurrence of PUFA / pufa in children aged 6-12 years at SD Negeri 023896 Binjai. This research is an analytical survey research with cross sectional design. total sample this research of 79 people were taken using the total sampling method. The analysis test used was chi-square. In this study, the influence of family support factors is p = 0.041 <0.05 and cost factor is p = 0.239> 0.05. The conclusion of this study that there is an influence of family support factors on the occurrence of PUFA / pufa and there is no influence cost factors on occurrence of PUFA / pufa. Kata Kunci: